Pain in multiple sclerosis: a systematic review of neuroimaging studies. - Seixas, D; Foley, P; Palace, J; Lima, D; Ramos, I; Tracey, I (Elsevier, 2014)
INTRODUCTION: While pain in multiple sclerosis (MS) is common, in many cases the precise mechanisms are unclear. Neuroimaging studies could have a valuable role in investigating the aetiology of pain syndromes. The aim of this review was to synthesise and appraise the current literature on neuroimaging studies of pain syndromes in MS. METHODS: We systematically searched PubMed and Scopus from their inception dates to the 2nd of April 2013. Studies were selected by predefined inclusion and exclusion criteria. Methodological quality was appraised. Descriptive statistical analysis was conducted. RESULTS: We identified 38 studies of variable methodology and quality. All studies but one used conventional structural magnetic resonance imaging, and the majority reported a positive association between location of demyelinating lesions and specific neuropathic pain syndromes. Most investigated headache and facial pain, with more common pain syndromes such as limb pain being relatively understudied. We identified a number of methodological concerns, which along with variable study design and reporting limit our ability to synthesise data. Higher quality studies were however less likely to report positive associations of lesion distribution to pain syndromes. CONCLUSIONS: Further high quality hypothesis-driven neuroimaging studies of pain syndromes in MS are required to clarify pain mechanisms, particularly for the commonest pain syndromes.